Kelompok Pelestari Lingkungan - Admin Jurnal Konservasi (Department of Forest Resources Conservation and Ecotourism - IPB University, 1991)
Environmental problem is social problem inclusive of some important social problem. That problem is faced by public in the same relative dimension and causes. Solution of social problem must social way especially institution aproximation.To rise and to develope Environmental Conservation Group (ECG) is an alternative solution environmental problem with institution aproximation. Basically ECG is informal institutional pleasent life norm that insight increased environmental quality with good planning.